RSG-GAS BASED RADIOISOTOPES AND SHARING PROGRAM FOR REGIONAL BACK UP SUPPLY - Soenarjo, Sunarhadijoso; Tamat, Swasono Rahardjo; Suparman, Ibon; Purwadi, Bambang (Jurnal Radioisotop dan Radiofarmaka, 2003)
ABSTRAK.RADIOISOTOP  BERBASIS  RSG-GAS  DAN PROGRAM KERJASAMA DUKUNGAN PASOKAN  REGIONALSebagai lembaga yang memiliki fasilitas reaktor untuk produksi radioisotop, BATAN perlu meningkatkan efektifItas biaya operasi reaktor melalui pencapaian pendayagunaan secara simultan keseluruhan fasilitas iradiasi yang tersedia dengan didukung pemanfaatan maksimal produk radioisotop yang dihasilkan. Di sisi lain, kebutuhan radioisotop di lingkungan domestik masih jauh di bawah kapabilitas maksimal produksi, tetapi ada kalanya pemenuhan kebutuhan radioisotop harus ditunda karena penyesuaian dengan jadwal operasi reaktor. Kondisi seperti ini teIjadi juga pada kebanyakan negara anggotaRCA (Bantuan KeIjasama Regional) - IAEA. Karena itu suatu program keIjasama dukungan pasokansediaan radioisotop secara regional merupakan pemikiran positif untuk pencapaian efektifItas biaya operasireaktor serta kesinambungan layanan dan pemanfaatan produk radioisotop yang  dihasilkan. Berdasarkan data hasil kegiatan produksi radioisotop domestik selama ini, maka radioisotop 311,9~0, J53Sm,12l dan 32pABSTRACT.RSG-GAS BASED RADIOISOTOPES AND SHARING PROGRAM FOR REGIONALBACK UP SUPPLY.As the owner of  the reactors used for radioisotope production, BATAN needs toincrease the effectiveness of the reactor operation cost that can be achieved by simultaneously exploiting allthe existing irradiation facility, supported by full utilization of the radioisotopes produced. On the other hand,the domestic demand of radioisotopes is much lower than the production capability but sometimes the requestis compulsory to be suspended due to reactor operation schedule. As this condition is mostly similar to that ofseveral countries of RCA Member States, a sharing program for regional back up supply seems to be apositive thought to support expectation on the effectiveness of reactor operation cost and the continuity ofradioisotope product services as well as the utilization of radioisotopes produced. Based on radioactivityachieved in each production batch at the present, 131r, 9~0, J53Sm,12srand 32pradioisotopes may be offeredfor back up supply program. Due to consideration on conformity of user demands with reactor operation andradiochemical processing costs, the concept of back up supply program should performed first by means offull utilization of the available products and not by increasing reactor operation frequency. An informationand communication network system, therefore, is absolutely needed to support infonnation exchange between the radioisotope producer, members of back up supply program and radioisotope customers.Key words: Radioisotopes production and supply, Reactor irradiation facility.